THE INFLUENCE OF QUALITY OF WORK LIFE AND SELF-EFFICACY ON JOB PERFORMANCE: THE MEDIATING ROLE OF JOB SATISFACTION AND THE MODERATING ROLE OF ORGANIZATIONAL COMMITMENT - Harefa, Tri Rahayu; Winadi, Ari Anggarani (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study seeks to elucidate the relationship between quality of work life (QWL) and self-efficacy and employee performance, with job satisfaction as a mediating factor and organizational commitment as a moderating variable. To achieve this, a survey was conducted involving the distribution of questionnaires to 171 educational staff members from Christian College Foundations in Jakarta, Central Java, and Surabaya. The findings reveal that QWL positively influences job satisfaction and employee performance, directly and indirectly affecting them through job satisfaction as a mediator. Interestingly, while self-efficacy positively impacts employee performance, it does not significantly affect job satisfaction. This suggests that employees' confidence in their abilities can enhance their performance, even if it does not necessarily lead to greater job satisfaction. Furthermore, organizational commitment does not significantly moderate the relationship between job satisfaction and employee performance. The study recommends cultivating a supportive work environment, boosting employee self-efficacy, and fostering a strong organizational commitment to enhance employee performance.JEL: J24, J28, O15.